Turning Cold Tumors Hot: Exploring Whether Val-boroPro and Val-boroPro and Doxorubicin Exhibit Synergy in the CT-26 Mouse Tumor Model. - Margosian, Victoria. (Tufts University. Tisch Library., 2019)
Val-boroPro, a compound first synthesized in the Bachovchin Lab at Tufts University Sackler School of Graduate Biomedical Sciences as a dipeptidyl aminopeptidase inhibitor, was found to stimulate the production of specific cytokines that enhance the immune response to tumors in a variety of mouse models. However, in these models, a criteria observed to mediate Val-boroPro's efficacy was the immunogenicity of the cancer cell line targeted for treatment. In non-antigenically visible cancers, Val-boroPro failed to elicit the same level of anti-cancer activity, as with those cancers that were known to be antigenically visible to the hosts immune system. This is feature that is common across immuno-oncology agents, as only immunogenic cancers elicit the recruitment of both the innate and the adaptive immune system. In contrast, those cancers that are not antigenically visible only recruit an innate immune response, which dramatically reduces their anti-cancer activity. Doxorubicin is an approved chemotherapeutic agent that interferes with DNA repair mechanisms, and causes cell death by necroptosis. Recent literature suggests that Doxorubicin is one of several chemotherapeutic agents that is able to induce immunogenic cell death of tumor cells. This inference followed the observation that Doxorubicin has greater anti-cancer activity in immune competent animals than in xenograft models. It is speculated that such a form of cell death might make the tumor antigenically visible to the hosts immune system. My masters' thesis hypothesizes that Val-boroPro will synergize with compounds such as doxorubicin that induce immunogenic cell death. To test this hypothesis, a combination of Val-boroPro and Doxorubicin were administered to Balb/c mice inoculated with syngeneic tumor model CT-26, which is a model for colon cancer, and for which Doxorubicin induced immunogenic cell death has been previously observed. The objective of my project was to determine if Val-boroPro immune enhancing activity could be harnessed in non-antigenically visible cancers when it was given with Doxorubicin.; Thesis (M.S.)--Tufts University, 2019.; Submitted to the Dept. of Pharmacology and Drug Development.; Advisors: William Bachovchin, and James Baleja.; Committee: William Bachovchin, and James Baleja.; Keyword: Pharmacology.